THE IMPACT OF OCCUPATIONAL HEALTH AND SAFETY (OHS) POLICIES ON EMPLOYEES' PSYCHOLOGICAL WELL-BEING IN SOPPENG CITY - Saraswaty, Aulia; Fadli, Zul (Program Studi Ilmu Administrasi Negara FISIP UNPATTI, 2024)
This study aims to evaluate the impact of Occupational Health and Safety (OHS) policies on the psychological well-being of employees in Soppeng City. Utilizing a comprehensive literature review method, data were gathered from a variety of sources including journal articles, books, and research reports. The primary objective was to analyze the relationship between OHS policies and the psychological well-being of employees. The findings from the review suggest that the effective implementation of OHS policies can significantly enhance employees' psychological well-being. This enhancement is achieved by increasing job security, reducing stress, and improving job satisfaction. Effective OHS policies have been shown to positively impact employees' mental well-being, which in turn contributes to increased productivity and loyalty to the company. Therefore, this study provides valuable recommendations for companies in Soppeng City. It suggests that these companies should strengthen their OHS policies to foster better employee well-being and cultivate a healthier work environment. The research underscores the importance of continuous support and regular training in maintaining optimal health and safety standards at the workplace. Furthermore, it emphasizes the need for ongoing evaluation and adaptation of OHS policies to address emerging challenges in the work environment. By doing so, companies can ensure sustained employee well-being and overall organizational health. The study highlights that such proactive measures are not only beneficial for employees but also advantageous for the companies, as they lead to a more motivated and committed workforce. In conclusion, well-implemented OHS policies are essential for promoting psychological well-being among employees, thereby enhancing both individual and organizational performance.